Design and optimization investigation on hydraulic transmission and energy storage system for a floating-array-buoys wave energy converter. (1st May 2021) - Sun, Pengyuan; Li, Qiang; He, Hongzhou; Chen, Hu; Zhang, Jun; Li, Hui; Liu, Dahui
Highlights: A floating-array-buoys wave energy converter (FABWEC) system is presented. A hydraulic transmission and accumulator system (HTAS) is designed and optimized. The mean output power of optimized HTAS can reach 5.8 kW based on simulated results. Optimized HTAS is practically applied to the next generation FABWEC prototype. Abstract: The energy density of wave power in China is relatively low compared with that of the wave power in Europe. Simply improving the shape or size of the energy-capturing mechanism for a wave energy converter (WEC) cannot directly result in a larger energy output. Instead, a solution of array-type energy-capturing mechanism integrating marine structure bares practical application potential to increase the power take-off (PTO) productivity. To exploit the conditions in China, a WEC system integrating oscillating-array-buoys with a floating platform is proposed and sea trials of a 10 kW prototype confirmed the feasibility of the floating-array-buoys WEC (FABWEC) system for wave energy conversion. However, sea trials data indicated that the energy conversion performance of the mechanical transmission design in the FABWEC system was relatively poor under the low wave energy density, suggesting the urgency of improving energy conversion and storage system to the increase of system performance. Herein, a hydraulic transmission and accumulator system (HTAS) is designed to replace the original mechanical transmission and flywheel system (MTFS), aiming to enhance the total energy conversion performance of the FABWEC system. The hydrodynamic simulation and numerical solution of the wave energy capture mechanism in the FABWEC system are carried out to facilitate the design and main components selection of the HTAS. And then the simulation and optimization of the designed HTAS are performed by the hydraulic simulation software. It is worth noting that there have been few reports on the operating performance of the HTAS with respect to buoys. In the hydraulic optimization process, the final optimization parameters of the HTAS are obtained by comparing the dynamic characteristics of the system, including system pressure, flow rate, motor torque and angular velocity, under the conditions with or without accumulator, with different buoy numbers and with different buoy phase differences. The simulated results show that the accumulator could effectively damp out the fluctuations in output power to turn the wave energy into a dispatchable power source; The energy conversion and output performances of the HTAS behave better with the increase of the buoys number and buoys phase difference, but the space and cost factors need to be taken into consideration in the actual operation; Within the research scope of this paper, the HTAS has an optimal performance for energy conversion and output when the number of buoys on one side of the floating platform is 5 and the phase difference between the buoys is 60°; Under the optimized conditions, the average output power of the hydraulic motor after stable operation of the HTAS can reach 5.8 kW. Significantly, the optimized HTAS could deliver the required electricity power steadily under the low wave energy density and has been practically applied to the next generation FABWEC prototype.